## Solving (x+4)(x+5)-30=0 in Factored Form

This problem involves solving a quadratic equation in factored form. Let's break down the steps:

### 1. Expand the Expression:

First, we need to expand the left side of the equation by multiplying the binomials:

(x+4)(x+5) - 30 = 0

**x² + 9x + 20 - 30 = 0**

### 2. Simplify the Expression:

Combine the constant terms:

**x² + 9x - 10 = 0**

### 3. Factor the Quadratic Expression:

Now, we need to find two numbers that multiply to -10 and add up to 9. These numbers are 10 and -1:

**x² + 10x - x - 10 = 0**

**x(x + 10) - 1(x + 10) = 0**

Now we can factor out (x + 10):

**(x + 10)(x - 1) = 0**

### 4. Solve for x:

For the product of two terms to be zero, at least one of them must be zero. Therefore:

**x + 10 = 0**=> x = -10**x - 1 = 0**=> x = 1

### Solution:

Therefore, the solutions to the equation (x+4)(x+5)-30=0 in factored form are **x = -10** and **x = 1**.